Automated/mechanized drilling and countersinking of airframes - Bullen, George N. (Society of Automotive Engineers, 2013)
The focus of this book is on automating the process of drilling and countersinking holes during airframe manufacturing. Since this is the area of greatest return on investment for airframe producers, the book provides a stepped approach for evaluating possible areas for applying automation and a detailed description of the process for choosing, acquiring, and transitioning the right machinery for success. It also provides a vision for a 10- to 15-year future state of airframe manufacture.
"SAE Order Number R-416"--Title page verso.
Title from PDF title page (SAE Web site, 07/25/2013).
Keywords: Rivets and riveting, Aircraft -- Automation.; Airframes -- Design and construction -- Automation.; Drilling and boring machinery -- Automation.; Manufacturing processes -- Automation.; Fasteners.; elektronické knihy; electronic books